Hepatitis B virus genotype D prevails in patients with persistently elevated or normal ALT levels in Turkey - Yalcin, K; Degertekin, H; Bahcecioglu, IH; Demir, A; Aladag, M; Yildirim, B; Badur, S (Springer Heidelberg, 2004)
Background: The clinical relevance of hepatits B virus (HBV) genotypes are poorly understood and it is unclear if the prevalence of HBV genotypes differs with the various clinical features of HBV carriers. The aim of our study was to examine the prevalence of the HBV genotype in a group of patients with chronic hepatitis B, compared to a group with chronic inactive hepatits B surface antigen (HbsAg) carriers. Patients and Methods: HBV genotypes were determined in 32 patients with chronic hepatitis B and in 12 chronic inactive HBsAg carriers. 35 males and nine females with a mean age of 33.95 +/- 13.04 were studied. Serum samples were examined for the presence of HBV DNA by polymerase chain reaction (PIER). Samples negative in first round PCR were further amplified with nested PCR. The PCR product was sequenced with the Cy5/5.5 dye primer kit on a Long Read Tower automated DNA sequencer. Results: HBV DNA was detectable in 29 (66%) and 44 (100%) patients by the PCR with universal primers and nested-PCR, respectively. All patients were found to be infected with HBV genotype D. Genotype D was the only detected type found in different clinical forms of chronic HBV infection, in all hepatitis B e antigen (HbeAg)-positive and negative patients, in at[ patients who had elevated or normal alanine transaminase (ALT) Levels and in all ages. Conclusion: In the present study we could not find any association between genotype D and distinct clinical phenotypes. Genotype D is the predominant type among hepatitis B carriers residing in our region and is not associated with more severe liver diseases. This genotype did not influence clinical manifestations in carriers with chronic hepatitis B virus infection. However, additional Large-scale longitudinal studies are needed to find the relationship of HBV genotypes to liver disease severity and clinical outcomes.
Keywords: Surface-Antigen; Hbv Infection; Core Promoter; Phylogenetic Relatedness; Nucleotide-Sequence; Central-America; Precore Region; Liver-Damage; Strains; Origin